Unregistered Customary Land Ownership: Implications and Challenges in Practice - Finna Maessy Pangestika; Mella Ismelina Farma Rahayu (Universitas Negeri Semarang, 2024)
In Indonesian culture, land is very important, especially when it comes to the ownership of unregistered customary property. This study seeks to evaluate the efficacy of the registration period outlined in Article 96 of Government Regulation No. 18/2021, along with the obstacles faced by the government in executing this policy. The study employs a normative legal approach with a qualitative descriptive methodology, examining applicable legislation and relevant literature. The results indicate that the specified registration timeframe could create legal ambiguity for landowners, particularly when several community members are either oblivious to the significance of registration or encounter barriers such as financial expenses and administrative processes. Although the Complete Systematic Land Registration (PTSL) initiative aims to optimize the registration process, insufficient public legal awareness may impede the attainment of land registration objectives. This study enhances comprehension of the effects of government policies on the rights of indigenous communities and provides recommendations to improve public participation in the land registration process, thus promoting greater legal certainty.